SARS‐CoV‐2 infection in pregnancy in Denmark—characteristics and outcomes after confirmed infection in pregnancy: A nationwide, prospective, population‐based cohort study. (31st August 2021) - Aabakke, Anna J. M.; Krebs, Lone; Petersen, Tanja G.; Kjeldsen, Frank S.; Corn, Giulia; Wøjdemann, Karen; Ibsen, Mette H.; Jonsdottir, F.; Rønneberg, Elisabeth; Andersen, Charlotte S.; Sundtoft, Iben; Clausen, Tine; et al.
Abstract: Introduction: Assessing the risk factors for and consequences of infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) during pregnancy is essential to guide clinical care. Previous studies on SARS‐CoV‐2 infection in pregnancy have been among hospitalized patients, which may have exaggerated risk estimates of severe outcomes because all cases of SARS‐CoV‐2 infection in the pregnant population were not included. The objectives of this study were to identify risk factors for and outcomes after SARS‐CoV‐2 infection in pregnancy independent of severity of infection in a universally tested population, and to identify risk factors for and outcomes after severe infection requiring hospital admission. Material and methods: This was a prospective population‐based cohort study in Denmark using data from the Danish National Patient Register and Danish Microbiology Database and prospectively registered data from medical records. We included all pregnancies between March 1 and October 31, 2020 and compared women with a positive SARS‐CoV‐2 test during pregnancy to non‐infected pregnant women. Cases of SARS‐CoV‐2 infection in pregnancy were both identified prospectively and through register linkage to ensure that all cases were identified and that cases were pregnant during infection. Main outcome measures were pregnancy, delivery, maternal, and neonatal outcomes. Severe infection was defined as hospital admission due to coronavirus disease 2019 (COVID‐19) symptoms. Results: Among 82 682 pregnancies, 418 women had SARS‐CoV‐2 infection during pregnancy, corresponding to an incidence of 5.1 per 1000 pregnancies, 23 (5.5%) of which required hospital admission due to COVID‐19. Risk factors for infection were asthma (odds ratio [OR] 2.19, 95% CI 1.41–3.41) and being foreign born (OR 2.12, 95% CI 1.70–2.64). Risk factors for hospital admission due to COVID‐19 included obesity (OR 2.74, 95% CI 1.00–7.51), smoking (OR 4.69, 95% CI 1.58–13.90), infection after gestational age (GA) 22 weeks (GA 22–27 weeks: OR 3.77, 95% CI 1.16–12.29; GA 28–36 weeks: OR 4.76, 95% CI 1.60–14.12), and having asthma (OR 4.53, 95% CI 1.39–14.79). We found no difference in any obstetrical or neonatal outcomes. Conclusions: Only 1 in 20 women with SARS‐CoV‐2 infection during pregnancy required admission to hospital due to COVID‐19. Risk factors for admission comprised obesity, smoking, asthma, and infection after GA 22 weeks. Severe adverse outcomes of SARS‐CoV‐2 infection in pregnancy were rare.